(untitled) (Research, Society and Development, 2020)
The objective this stud was to evaluate the antimicrobial activity of essential oils (organic vs. conventional) of Origanum vulgare L. in the action against Candida albicans, Escherichia coli and Staphylococcus aureus. The inoculation of rhizobacteria (environmental (ME) and Bacillus subtilis) potentiated the antimicrobial action. The essential oils of Traditional (organic) cultivation presented antibacterial action and antifungal, while the essential oil of conventional cultivation (NPK) showed no any antibacterial or antifungal activity. It was concluded that the formulation of vermicomposting and the use of rhizobacteria are potential technologies and tools for family farmers and traditional community in the cultivation of orégano.